Diagnostics and Treatment of Cerebral Venous Thrombosis - G. R. Ramazanov; Kh. V. Korigova; S. S. Petrikov (Неотложная медицинская помощь, 2021)
BACKGROUND This article is devoted to the discussion of a life-threatening and difficult to diagnose disease — cerebral venous thrombosis (CVT). The article lists clinical manifestations, features of diagnosis and treatment of CVT. Cerebral venous thrombosis is an emergency that requires a quick decision to start therapy in order to prevent the development of venous cerebral infarction, intracranial hemorrhage, severe disability and death. Cerebral venous thrombosis is a rare and rather difficult to recognize form of acute cerebrovascular accident (ACVA). Considering the variability of the clinical and radiological picture, as well as the large number of risk factors, CVT is a complex medical problem. Despite the fact that CVTs account for less than 1% of all ACVA, significant differences in treatment necessitatethe earliest possible differential diagnosis of CVT with arterial stroke. The diagnosis is often made with a delay due to a wide range of clinical manifestations, subacute onset of the disease, as well as low alertness of specialists in relation to CVT. In patients with cryptogenic stroke, CVT should be ruled out as a potential cause of stroke. Among other things, in the case of CVT, as in the case of thrombosis of the cerebral arteries, the establishment of the leading etiological factor is one of the priority tasks, the solution of which allows choosing the optimal means of secondary prevention. AIM OF STUDY Raising awareness of doctors of multidisciplinary hospitals about clinical manifestations, methods of diagnosis and treatment of CVT.MATERIAl AND METHODS To achieve this goal, the results of domestic and foreign scientific research on the diagno-sis and treatment of CVT were analyzed. Literature searches were carried out in electronic search engines Scopus, eLibrary, PubMed using the keywords: cerebral venous thrombosis, cryptogenic stroke, intracerebral hemorrhage, anticoagulant therapy, neurological imaging in cerebral venous thrombosis. For the analysis, scientific articles published between 1828 and 2020 were selected. Thirty percent of the analyzed works on the subject of CVT are not older than 5 years.CONClUSION Due to the various clinical manifestations and the absence of pathognomonic symptoms, neuroimaging plays a leading role in establishing the diagnosis. Early diagnosis of cerebral venous thrombosis and the use of anticoagulants lead to a decrease in disability and mortality.